RONC-15. OUTCOMES OF BRAIN AND SKULL-BASE TUMOURS IN ADOLESCENTS AND YOUNG ADULTS TREATED WITH PENCIL BEAM SCANNING PROTON THERAPY. (4th December 2020) - Lim, Pei Shuen; Tran, Sébastien; Kroeze, Stephanie G C; Pica, Alessia; Hrbacek, Jan; Bachtiary, Barbara; Walser, Marc; Lomax, Anthony J; Weber, Damien C
Abstract: BACKGROUND: The use of highly conformal proton therapy in adolescents and young adults (AYAs) for management of brain/skull-base tumours is becoming increasingly common. This study aims to assess the long-term clinical outcomes, prognostic factors and employment status of AYAs (15–39 years) treated with pencil-beam-scanning proton-therapy (PT). METHODS: Between 1997–2018, 176 AYAs were treated with PT at the Paul Scherrer Institute. Median age was 30 years (range, 15–39) and the male/female ratio was 0.8. RESULTS: After a median follow-up of 66 months (range, 12–236), 24 (13.6%) local failures and 1 (0.6%) distant failure were observed between 6 and 152 months after PT. The most common histologies treated were chordomas/chondrosarcomas (61.4%), followed by meningiomas (14.2%) and gliomas (15.3%). The 6-year local-control (LC), distant-progression-free survival and overall-survival (OS) rate was 83.2%, 97.4% and 90.2% respectively. On univariate analysis, age ≥24 years was a negative prognostic factor for LC. Recurrent disease, infratentorial tumours and low-grade-glioma histology were poor prognostic factors for both LC and OS. The 6-year ≥G3 PT-related late toxicity-free survival was 88.5%. The moderate-high grade late toxicity crude rates were 37.8% G2, 12.2% G3, 0.6% G4 and 0.6% G5. No secondary malignancies were observed. The unemployment rate was 7.3% at PT, rising to 25.3% at survivorship. High-grade(≥G3) toxicity rate in the unemployed vs employed group was 21% vs 8.5%. CONCLUSION: PT is an effective treatment for AYAs with brain/skull-base tumours with good tumour control and acceptable long-term toxicity. Despite having satisfactory clinical outcomes, around 1 in 4 AYAs surviving brain/skull base tumours are unemployed.